MANAGEMENT RESEARCH METHODS - S. Sangadji, Suwandi (PROCURATIO: Jurnal Manajemen & Bisnis, 2023)
This reference is a comprehensive and valuable resource for both novice and experienced researchers in the field of management. Published by Cambridge University Press, the book guides readers through the entire research process, covering essential aspects such as research design, data collection methods, measurement techniques, data analysis, and ethical considerations. It provides a wealth of knowledge and practical insights to conduct management research effectively. The review aims to provide an in-depth analysis of the book's content and its significance in the field. The authors introduce fundamental research concepts, emphasizing the importance of clear research questions and hypotheses, and delve into research paradigms and ethics, thus laying a solid foundation for readers. Furthermore, the book explores various research designs, data collection methods, and measurement principles, equipping researchers with essential tools for their studies. In Section 5, data analysis is discussed, covering both quantitative and qualitative techniques, and presented in an easy-to-understand manner. The final section emphasizes the importance of ethical considerations and effective communication in reporting research results. Overall, the book serves as an indispensable resource, catering to a diverse audience and promoting ethical research practices in the management domain.